Quetiapine treatment for cannabis use disorder. (1st January 2021) - Mariani, John J.; Pavlicova, Martina; Jean Choi, C.; Basaraba, Cale; Carpenter, Kenneth M.; Mahony, Amy L.; Brooks, Daniel J.; Bisaga, Adam; Naqvi, Nasir; Nunes, Edward V.; Levin, Frances R.
Highlights: In a 12-week randomized double-blind placebo-controlled trial, the efficacy of quetiapine 300 mg for the treatment of CUD was tested in 130 outpatients. Weekly cannabis use was categorized into three groups: high use (5–7 days), medium use (2–4 days) and low use (0–1 days). The use of quetiapine to treat CUD was associated with an increased likelihood of high frequency use transitioning to medium use, but not low use. Abstract: Backround: Pharmacotherapy for cannabis use disorder (CUD) is an important unmet public health need. Methods: In a 12-week randomized double-blind placebo-controlled trial, the efficacy of quetiapine (300 mg nightly) for the treatment of CUD was tested in 130 outpatients. Weekly cannabis use was categorized into three groups: heavy use (5−7 days), moderate use (2–4 days) and light use (0–1 days). Results: At baseline both groups were considered heavy users (using days per week: median = 7.0; interquartile range (IQR): 6.5−7.0; daily dollar value: median = $121.4; IQR: 73.8–206.3). The week-by-treatment interaction was marginally significant (χ 2 (2) = 5.56, P  = .06). With each week, the odds of moderate compared to heavy use significantly increased in the quetiapine group (OR=1.17, P  < .0001), but not significantly in the placebo group (OR=1.05, P  = .16). The odds of light versus heavy use did not significantly differ over time ( P  = .12). Treatment was also associated with reduced cannabis withdrawal symptoms by 10.4% each week (95% CI: 8.9–11.8). No serious adverse events occurred during the study and no evidence of development of a movement disorder was detected. Adverse effects were not significantly different between the quetiapine and placebo treatment arms. Conclusions: The use of quetiapine to treat CUD was associated with an increased likelihood of heavy frequency use transitioning to moderate use, but not light use. The clinical significance of reductions in cannabis use, short of abstinence warrants further study.